Understanding the linear and nonlinear optical responses of few-layer exfoliated MoS2 and WS2 nanoflakes: experimental and simulation studies. (22nd October 2022) - Abhijith, T; E, Shiju; Suthar, Rakesh; Sharma, Punit; Thomas, Sheenu; Karak, Supravat
Abstract: Understanding the linear and nonlinear optical (NLO) responses of two-dimensional nanomaterials is essential to effectively utilize them in various optoelectronic applications. Here, few-layer MoS2 and WS2 nanoflakes with lateral size less than 200 nm were prepared by liquid-phase exfoliation, and their linear and NLO responses were studied simultaneously using experimental measurements and theoretical simulations. Finite-difference time-domain (FDTD) simulations confirmed the redshift in the excitonic transitions when the thickness was increased above 10 nm indicating the layer-number dependent bandgap of nanoflakes. WS2 nanoflakes exhibited around 5 times higher absorption to scattering cross-section ratio than MoS2 nanoflakes at various wavelengths. Open aperture Z scan analysis of both the MoS2 and WS2 nanoflakes using 532 nm nanosecond laser pulses reveals strong nonlinear absorption activity with effective nonlinear absorption coefficient ( β eff ) of 120 cm GW −1 and 180 cm GW −1, respectively, which was attributed to the combined contributions of ground, singlet excited and triplet excited state absorption. FDTD simulation results also showed the signature of strong absorption density of few layer nanoflakes which may be account for their excellent NLO characteristics. Optical limiting threshold values of MoS2 and WS2 nanoflakes were obtained as ∼1.96 J cm −2 and 0.88 J cm −2, respectively, which are better than many of the reported values. Intensity dependent switching from saturable absorption (SA) to reverse SA was also observed for MoS2 nanoflakes when the laser intensity increased from 0.14 to 0.27 GW cm −2 . The present study provides valuable information to improve the selection of two-dimensional nanomaterials for the design of highly efficient linear and nonlinear optoelectronic devices.